Penggunaan metode pembelajaran berbasis cooverative learning dengan menerapkan media puzzle untuk meningkatkan pemahaman dan keaktifan belajar siswa pada pembelajaran ilmu pengetahuan alam dengan materi proses pembentukan uruine pada siswa kelas VII MTS - Hapipa, Ivi; Cahaya Cipta, Yosita (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study aims to improve grade VIII students’ understanding and learning activity in science, particularly the urine formation process at MTs Ja Al-Haq, Bengkulu City. The material includes complex stages—filtration, reabsorption, and secretion—that students often find difficult. Therefore, cooperative learning supported by puzzle media was implemented to create a more engaging and interactive learning environment.This research used Classroom Action Research (CAR) with two cycles consisting of planning, implementation, observation, and reflection. The subjects were 32 eighth-grade students. Data were collected through concept understanding tests, observation sheets, and interviews.The results showed that the cooperative learning method with puzzle media effectively improved students’ understanding and learning activity. Students became more active in discussions, asked more questions, and expressed their opinions more confidently. Test scores also increased significantly by the end of the second cycle.In conclusion, cooperative learning assisted by puzzle media is an effective alternative to enhance students’ understanding and participation in science learning, especially on the urine formation topic